Gamification in online learning: a case study among university students in Malaysia / Nor Azairiah Fatimah Othman ... [et al.] - Othman, Nor Azairiah Fatimah; Jaini, Azila; Ismail, Mazida; Zainoddin, Amir Imran; Mohamad Radzi, Siti Fatimah; Kaliani Sundram, Veera Pandiyan (Universiti Teknologi MARA, 2023)
Online learning has become compulsory when the world was facing the Covid 19 outbreak. Accordingly, students’ engagement and participation during online learning have been a major concern among teachers. By adapting the Technology Acceptance Model (TAM), the present study is carried out to examine influential factors towards the intention to use gamification during online classes. With the use of judgmental sampling, 283 usable responses have been gathered from undergraduate students in Malaysia. Results revealed that ‘authentic’ positively affects three mediating variables of perceived value (PEU), perceived usefulness (PU) and perceived enjoyment (PE). Additionally, PEU, PU and PE posit positive responses towards the intention to use gamification in online learning. Furthermore, all three mediators also present positive effects in the relationship between authentic and intention to use. Thus, this study affirms the usability of TAM in the online learning context with the extension of authenticity as the external factor and perceived enjoyment as the mediating factor. The results give implications for educators and higher learning institutions to modify their learning outcomes and course content to be more interesting with the usage of online gamification tools. Perhaps, this study gives further insight for future research to apply other external factors, such as knowledge and trust to enrich the study in gamification context.